Allergic and immunologic evaluation of children with celiac disease - Demirtaş Güner, Duygu; Baskın, Kübra (Frontiers in Pediatrics, 2025)
IntroductionCeliac disease (CD) and allergic diseases are immune-mediated disorders with overlapping clinical and immunologic features. The association between CD and selective immunoglobulin (Ig) A deficiency (sIgAD) is well-established, but limited data exist on the relationship between CD, other antibody deficiencies, and allergic diseases in children. This study aimed to evaluate the prevalence of allergic manifestations and immunologic abnormalities in children with CD.MethodsThis prospective study included children with biopsy-confirmed CD, followed at a gastroenterology clinic from August 2022 to February 2023. Participants underwent comprehensive immunologic and allergic evaluation, including serum immunoglobulin levels, vaccine antibody responses, lymphocyte subgroup analysis, and allergy testing as clinically indicated.ResultsThe cohort included 76 patients with a median age of 11 years and a median age at CD diagnosis of 5.8 years. Allergic manifestations included aeroallergen sensitivity (22.4%), allergic rhinitis (15.8%), allergic conjunctivitis (13.2%), food allergy (5.3%), and asthma and eczema (3.9% each). Immunologic evaluations revealed normal profiles in 69.7% of patients, while abnormalities included partial IgM deficiency (6.6%), unclassified hypogammaglobulinemia (5.3%), sIgAD (2.6%), and transient hypogammaglobulinemia of infancy (2.6%). Elevated IgE levels were observed in 13.2% of patients.ConclusionThis study highlighted a significant prevalence of allergic diseases and immunologic abnormalities in children with CD, extending beyond the commonly recognized association with sIgAD. These findings underscore the importance of comprehensive immunologic and allergic evaluation in children with CD.